ANALISIS KINERJA BADAN USAHA MILIK DESA (BUMDES) TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA SANGGA LIMA KECAMATAN GEBANG KABUPATEN LANGKAT PERIODE TAHUN 2021-2022 - Windiani; Abdullah Sani; Asmawarna Sinaga (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study focuses on discussing the performance of village-owned enterprises (BUMDES) in improving the welfare of the community in Sangga Lima Village, Gebang District, Langkat Regency for the 2021-2022 period. The research method used in this study is a descriptive qualitative research method with an empirical approach. The informants in this study were management and 30 customers of BUMDES Sangga Lima, Gebang District, Langkat Regency for the 2021-2022 period. The results of the study explain the performance of Village-Owned Enterprises (BUMDES) in Sangga Lima Village, Gebang District, Langkat Regency for the 2021-2022 period, namely carrying out various activities such as business loan funds, providing seminars, training, and consulting in managing businesses. The performance of village-owned enterprises (BUMDES) in Sangga Lima Village, Gebang District, Langkat Regency for the 2021-2022 period has affected the welfare of the community and has been able to improve their economy and business, compared to before receiving BUMDES loans, consultations and guidance. There has been an increase in Community Welfare in Sangga Lima Village, Gebang District, Langkat Regency for the 2021-2022 period which can be seen from various indicators such as increasing people's income so that they can meet their daily needs such as food, as well as other needs such as housing, family health and the need for education their children.